PENGGUNAAN MEDIA AUDIO-VISUAL PADA MATA PELAJARAN ILMU PENGETAHUAN ALAM DI SEKOLAH MENENGAH PERTAMA NEGERI 1 PACITAN - PURWONO, JONI (Jurnal Teknologi Pendidikan dan Pembelajaran, 2014)
The purposes of this study were (1) to know the teacherâs planning in using the audiovisual media on Science subject at SMP Negeri 1 Pacitan, (2) to know the skill of teacher in using the audio visual media on Science subject at SMP Negeri 1 Pacitan, (3) to know the barriers in using the audiovisual media on Science subject at SMP Negeri 1 Pacitan, and (4) to describe the learning outcome of students in using the audiovisual media on Science subject at SMP Negeri 1 Pacitan.This study was conducted using a qualitative approach and descriptive methods. The data collected in this study based on interviews, field observations and documents, in the form of pictures and notes on the school profile. The respondents of this study were students of SMP Negeri 1 Pacitan in the 2012/2013 Academic Year, class VII, VIII, and IX, all of the science teachers and the principal. The results of this research showed that in planning, the science teachers paid attention to the competence standards contained in the Education Unit Level Curriculum (SBC) so that the direction and learning objectives can be achieved optimally and also consider the availability of facilities and infrastructure. The teachersâ skills are sufficient and competent enough but needs to be improved by folowing trainings, workshops, or invite the relevant instructors. The problems in the form of technical and non-technical constraints were generally not a problem and can besolved by the creativity of teachers to maximize the existing infrastructure. Student learning out come after using audio-visual media was increased, it means with the use of audio-visual media in the studentsâ absorbsion was increased.The implementation of teaching learning process in science at SMP Negeri 1 Pacitan by using audio-visual media ran very interactively and enthusiasticly, students became more motivated to keep learning.Â Keywords: audiovisual media, Science, achievement